2007
DOI: 10.1002/9783527621286.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic Approaches for Measuring Log P

Abstract: AbbreviationsADMET absorption, distribution, metabolism, elimination and toxicity CE capillary electrophoresis CHI chromatographic hydrophobicity index IAM immobilized artifi cial membrane LC liguid chromatography LEKC/VEKC liposome/vesicular electrokinetic chromatography LSER linear solvation energy relationship LSS linear solvent strength MEEKC microemulsion electrokinetic chromatography MEKC micellar electrokinetic chromatography MS mass spectrometry ODP octadecyl polyvinyl ODS octadecylsilane OS octylsilan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 83 publications
0
23
0
Order By: Relevance
“…-Thirty-eight analytes with log P oct values ranging from 0 to 5 were selected by cluster analysis to obtain a well-balanced set of compounds in terms of molecular chemical properties [10]. Based on their calculated CLogP values (between 5 and 8), 14 rigid compounds were chosen to avoid problems related to the neglect of molecular 3D-structure effects in lipophilicity prediction [3]. The log k w values of the 52 compounds were determined under their neutral form with three different stationary phases (Discovery RP Amide C16 with HPLC system, and Acquity BEH Shield RP18 and Hypersil TM GOLD Javelin HTS with UHPLC system), and different experimental conditions were evaluated with each column: i) isocratic mode with MeOH as organic modifier, ii) gradient mode with MeOH, and iii) isocratic mode with MeCN.…”
mentioning
confidence: 99%
“…-Thirty-eight analytes with log P oct values ranging from 0 to 5 were selected by cluster analysis to obtain a well-balanced set of compounds in terms of molecular chemical properties [10]. Based on their calculated CLogP values (between 5 and 8), 14 rigid compounds were chosen to avoid problems related to the neglect of molecular 3D-structure effects in lipophilicity prediction [3]. The log k w values of the 52 compounds were determined under their neutral form with three different stationary phases (Discovery RP Amide C16 with HPLC system, and Acquity BEH Shield RP18 and Hypersil TM GOLD Javelin HTS with UHPLC system), and different experimental conditions were evaluated with each column: i) isocratic mode with MeOH as organic modifier, ii) gradient mode with MeOH, and iii) isocratic mode with MeCN.…”
mentioning
confidence: 99%
“…Clear differences in passive permeability could be evidenced for the different constituents of the extracts. Such dissimilarities between these profiled metabolites could not simply be based on their polarity (such as their retention times [50,51]). These findings have also indicated that the presence of multiple component mixtures did not influence the passive permeability of single constituents and thus that the passive absorption of NPs seemed not to be potentially influenced by synergistic aspects in the frame of the HDM-PAMPA predictions.…”
mentioning
confidence: 99%
“…This issue can be solved (i) by adding 1-octanol to the mobile phase, which acts as a weak masking agent reducing secondary interactions due to residual silanol groups but with long equilibration times [20,21] Electrophoresis 2010, 31, 952-964 952 by using isocratic log k values measured at 50% methanol [17,18]. In this context, CE is emerging as an attractive technique for log P determination thanks to numerous advantages: (i) small solvent and sample consumption, (ii) highly pure samples not needed, (iii) automation, and (iv) low cost [13][14][15][22][23][24][25][26].For lipophilicty determination by CE, it is necessary to work with a BGE allowing the separation of neutral compounds. Different CE modes have been tested, namely MEKC, MEEKC, and LEKC/VEKC (micellar, microemulsion (ME) and liposome/vesicle EKC, respectively).…”
mentioning
confidence: 98%
“…However, this technique is only appropriate for ionizable compounds and requires milligram amounts of pure sample. The LC approach is a good alternative as it presents some inherent advantages: (i) small sample consumption, (ii) highly pure samples not required due to its separation power, (iii) automation, and (iv) wide range of measurable log P oct values (from À1 to 8) [11,[13][14][15][16]. Furthermore, HTS methods have been reported thanks to the recent development of ultra high pressure liquid chromatography (UHPLC) [17,18].…”
mentioning
confidence: 99%